Islamic education curriculum planning at SDIT Putra Pakuan Bogor - Anwar Siroz; Endin Mujahidin; Muhammad Chafidz Ali Wafa (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines Islamic education curriculum planning as a strategic effort to achieve holistic educational goals at SDIT Putra Pakuan Bogor. Using a literature review method, the research highlights the integration of scientific knowledge and Islamic values, a needs-based planning process, and a curriculum structure that combines national and Islamic education frameworks. The main challenges in curriculum implementation include resource limitations and policy changes. However, these challenges can be overcome through innovative strategies such as teacher training and educational technology integration. Regular evaluations are conducted to ensure that the curriculum remains relevant to contemporary needs. The study's findings emphasize the importance of Islamic curriculum principles, such as flexibility, relevance, and integrity, in shaping academically excellent and morally upright students. This research contributes to the development of an adaptive and high-quality Islamic education curriculum in Indonesia.